An expanded population of pathogenic regulatory T cells in giant cell arteritis is abrogated by IL-6 blockade therapy. Issue 5 (7th December 2016) - Miyabe, Chie; Miyabe, Yoshishige; Strle, Klemen; Kim, Nancy D; Stone, John H; Luster, Andrew D; Unizony, Sebastian
Abstract : Objectives: Randomised-controlled trials have recently proven the efficacy of the interleukin (IL)-6 receptor antagonist tocilizumab (TCZ) in giant cell arteritis (GCA). However, the mechanism of action of IL-6 blockade in this disease is unknown. Moreover, the role of regulatory T (Treg) cells in the pathogenesis of GCA remains underexplored. Given the plasticity of Tregs and the importance of IL-6 in their biology, we hypothesised that TCZ might modulate the Treg response in GCA. We therefore characterised the Treg compartment of patients with GCA treated with TCZ. Methods: We classified 41 patients with GCA into three groups: active disease (aGCA, n=11), disease remission on corticosteroids (rGCA-CS, n=19) and disease remission on TCZ (rGCA-TCZ, n=11). Healthy controls (HCs) were included for comparison. We determined the frequency, phenotype and function of peripheral blood Tregs. Results: Patients with aGCA demonstrated a hypoproliferating Treg compartment enriched in IL-17-secreting Tregs (IL-17 + Tregs). Tregs in patients with aGCA disproportionally expressed a hypofunctional isoform of Foxp3 that lacks exon 2 (Foxp3Δ2). Foxp3Δ2-expressing Tregs coexpressed CD161, a marker commonly associated with the Th17 linage, significantly more often than full-length Foxp3-expressing Tregs. Compared with those of HCs, GCA-derived Tregs demonstrated impaired suppressor capacity. Treatment with TCZ, in contrast to CS therapy, corrected the Treg abnormalities observed in aGCA. In addition, TCZ treatment increased the numbers of activated Tregs (CD45RA − Foxp3 high ) and the Treg expression of markers of trafficking (CCR4) and terminal differentiation (CTLA-4). Conclusions: TCZ may exert its therapeutic effects in GCA by increasing the proliferation and activation of Tregs, and by reverting the pathogenic Treg phenotype seen during active disease.